Clinical effectiveness of golimumab in Crohn's disease: an observational study based on the Swedish National Quality Registry for Inflammatory Bowel Disease (SWIBREG). (2nd November 2018) - Rundquist, Sara; Eriksson, Carl; Nilsson, Linda; Angelison, Leif; Jäghult, Susanna; Björk, Jan; Grip, Olof; Hjortswang, Henrik; Strid, Hans; Karlén, Per; Montgomery, Scott; Halfvarson, Jonas
Abstract: Objective: The effectiveness of golimumab in Crohn's disease (CD) is largely unknown as it is not approved for the treatment of the disease. We aimed to identify the population of CD patients treated with golimumab in Sweden, to assess the effectiveness of golimumab (defined as the drug retention rate), and to identify predictors of drug discontinuation. Methods: Patients with CD who received at least one injection of golimumab were identified through the Swedish National Quality Registry for Inflammatory Bowel Disease, which includes prospectively collected clinical information. Cox regression models were used to identify predictors of golimumab discontinuation. Results: The study cohort involved 94 patients of whom the majority (96.8%) had previously discontinued at least one anti-tumour necrosis factor (anti-TNF) agent. The drug retention rate at 12 weeks was 85.1%. Predictors of golimumab discontinuation at 12 weeks were previous surgery (adjusted HR = 7.52, 95% CI: 1.12–50.36), concomitant corticosteroid use at baseline (adjusted HR = 5.70, 95% CI: 1.13–28.68) and female sex (adjusted HR = 6.59; 95% CI: 1.04–41.62). The median duration of follow-up was 89 (IQR: 32–158) weeks. The drug retention at the most recent follow-up was 35.1%. Predictors of golimumab discontinuation at the most recent follow-up were corticosteroid use at baseline (adjusted HR = 2.60, 95% CI: 1.17–5.79) and female sex (adjusted HR = 2.24; 95% CI: 1.19–4.23). Conclusion: Patients with CD treated with golimumab were a treatment-refractory group. Despite this, more than one-third of the patients appeared to have had clinical benefit after a median follow-up of more than 1.5 years.